STATUS HEMOGLOBIN, KEBIASAAN MEROKOK DAN DAYA TAHAN KARDIORESPIRASI (VO2 MAX) PADA ATLET UNIT KEGIATAN MAHASISWA BOLA BASKET [Haemoglobin Status, Smoking Habits and Cardiorespiratory Endurance (Vo2 max) among Basketball Student Activity Units] - Lidya Anggraeni; R. Bambang Wirjatmadi (Media Gizi Indonesia, 2019)
Basketball athlete require maximum oxygen capacity to maintain their endurance during physical activity for long time. Good cardio respiratory endurance for athlete can slower fatigue so they can reach a peak performance optimally. Many factors affect cardio respiratory endurance such as haemoglobin status and smoking habits. The purpose of this study was to analyze the correlations between haemoglobin status and smoking habits with cardio respiratory endurance among basketball student activity unit. This research was an observational analytic with case control study design. The sample in this research were 50 people and divided into case (25 people) and control (25 people) groups. Data collections included cooper test, blood sampling with cyanmethemoglobin method and smoking habits. The result showed that there were correlation between haemoglobin status p=0.014 (OR = 6.78; 95% CI: 1.6-28.54), smoking habits p=0.020 (OR = 7.67; 95% CI: 1.47-39.98) with cardio respiratory endurance. Non anemia and non-smoking Athletes have a better cardio respiratory endurance than anemia and smoking athletes. It is recommend to maintain haemoglobin status in the normal range to avoids anemia and quit smoking to increase their optimal cardio respiratory endurance